Fungsi Tangsi Belanda Setelah Revitalisasi 2018 di Kecamatan Mempura Kabupaten Siak dalam Bidang Pendidikan dan Sosial Ekonomi - Miranda Miranda; Isjoni Isjoni; Asril Asril (Universitas Veteran Bangun Nusantara, 2023)
Siak Sri Indrapura is one of the capitals in Riau province, Siak is a developing area and is known for its Malay historical sites which are still very thick, this statement is supported by various historical facts, that's why the Siak Regency Government introduced the slogan Siak The Truly Malay at the Tour de Siak event in 2013. The government realizes the potential of Siak which is rich in traditional, historical and cultural values, the government proposes this area as a heritage city area or a city that has cultural and historical richness that must be preserved. One of the historical relics that are still enjoyed today, both local and foreign, are the Siak Palace and the Dutch Tangsi. The Dutch Tangsi also has a very high architectural value because the building has a European nuance which is equipped with small rooms for weapons storage, prison rooms, and office spaces. The purpose of this research; (1) To analyze how the history and purpose of the Dutch Tangsi was built. (2) To analyze how the function of the Dutch Tangsi after the revitalization. (3) To analyze how the impact of the revitalization of the Dutch Tangsi in the field of education. (4) To analyze how the impact of the revitalization of the Dutch Tangsi in the socio-economic field. In this study, the author uses a qualitative research method. This research study uses a qualitative descriptive approach, namely an approach that in data management since reducing, presenting and verifying and concluding data, does not use systematic and statistical calculations, but rather emphasizes interpretative studies. The method refers to the techniques used in research such as surveys, interviews and observations.